2017
DOI: 10.3390/molecules22111629
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bioactivity Assessment of Chitosan-1-Acetic Acid-5-Flurouracil Conjugates as Cancer Prodrugs

Abstract: 5-fluorouracil (5-FU) is a specific anti-cancer agent that is generally used to treat gastrointestinal, colorectal, and breast cancer. In this work, chitosan (CS) was extracted from local fish scales using an established method. 5-FU was then converted to 1-acetic acid-5-fluorouracil (FUAC) and reacted with this CS to prepare chitosan-1-acetic acid-5-fluorouracil (CS-FUAC) conjugates as a colon-specific prodrug. All compounds were characterized by Proton nuclear magnetic resonance (1H-NMR), Fourier-transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…17 , 18 Its molecular structure is similar to that of cellulose except for the presence of a primary amino group in the C2 position of the anhydroglucose unit. 19 This structural similarity allows blending cellulose and chitosan into a homogeneous matrix. These properties make chitosan an attractive doping agent to increase the yield of the cellulose-based CF precursor filaments without significant impairment of the mechanical property.…”
Section: Introductionmentioning
confidence: 99%
“…17 , 18 Its molecular structure is similar to that of cellulose except for the presence of a primary amino group in the C2 position of the anhydroglucose unit. 19 This structural similarity allows blending cellulose and chitosan into a homogeneous matrix. These properties make chitosan an attractive doping agent to increase the yield of the cellulose-based CF precursor filaments without significant impairment of the mechanical property.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on other molecules, such as the novel organic nitrate RS-7897, have shown that hydrolysis of an amide bond can release more active molecules than the parent molecule 25. Furthermore, amide bonds are often incorporated into drug designs, as a linker to tether a drug to a targeting peptide 26.…”
Section: Introductionmentioning
confidence: 99%
“…Then 4 h later, the solution on the plate was removed and the content was dissolved with DMSO [33]. The absorption was measured at 490 nm and cell viability was calculated, cell viability% = OD of treated cells/OD of untreated cells × 100% [51].…”
Section: Methodsmentioning
confidence: 99%